2014
DOI: 10.1155/2014/505368
|View full text |Cite
|
Sign up to set email alerts
|

The Higher Plasma Malondialdehyde Concentrations Are Determined by Metabolic Syndrome-Related Glucolipotoxicity

Abstract: This study aimed to elucidate the determinants of higher plasma malondialdehyde (MDA) in free-living adults. In a cross-sectional study we evaluated 148 free-living subjects (54 ± 11 years, 78% women) at high risk for or with metabolic syndrome (MetS). They were assessed by anthropometry and body composition, dietary intake, and clinical and laboratorial analysis. The analysis of plasma MDA was performed by HPLC, and concentration values were used to provide four groups according to percentile distribution. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
5
28
0
3
Order By: Relevance
“…Previous study showed that negative energy balance provided by our LiSM protocol can favor insulin sensitivity, resulting in better glucose metabolism control [35]. Although neither glucose nor MDA levels changed significantly, it was possible to observe that they have synergistically effects [36]. Controlling glucose metabolism can efficiently diminish glycation processes.…”
Section: Discussionmentioning
confidence: 83%
“…Previous study showed that negative energy balance provided by our LiSM protocol can favor insulin sensitivity, resulting in better glucose metabolism control [35]. Although neither glucose nor MDA levels changed significantly, it was possible to observe that they have synergistically effects [36]. Controlling glucose metabolism can efficiently diminish glycation processes.…”
Section: Discussionmentioning
confidence: 83%
“…MDA is known to generate secondary products of lipid peroxidation, reflecting the magnitude of the oxidative stress present in the organism [27]. Furthermore, the MetS prevalence was greater in participants with higher plasma MDA concentrations [28]. The mechanism that leads to a higher aPWV with increased MDA is still unclear.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…El MDA, producto final de la lipoperoxidación, es utilizado ampliamente como biomarcador de estrés oxidativo, en cuyo metabolismo forma malodialdehido acetaldehído (MAA), que finalmente se une a los grupos aminos de las proteínas, comportándose como proteína inmunogénica o autoanticuerpo que activa mecanismos fisiopatológicos de la ateroesclerosis, la diabetes mellitus, la preeclamsia, la enfermedad de Parkinson y la enfermedad de Alzheimer (13)(14)(15)(16)(17) .…”
Section: Discussionunclassified
“…Está definido que en un ambiente de hipoxia hipobárica, se generan mayor cantidad de RL, asimismo, se ha evidenciado el papel del estrés oxidativo en el debut de enfermedades denominadas propias de la altura, sean estas de presentación aguda o crónica, como el mal agudo de montaña y el mal crónico de montaña entre otras, asimismo, el estrés oxidativo cumple un papel importante en la génesis de enfermedades como la hipertensión arterial sistémica, la hipertensión pulmonar, la enfermedad renal, la fibrosis pulmonar, el asma, y la esclerosis lateral amiotrófica (13)(14)(15)(16) .…”
Section: Discussionunclassified